Effects of dried sugar beet root based concentrates level on the performance of Nubian goat male kids - Elimam, Mohamed; Musa, Areeg; Siddig, Fawgia (Gezira Journal of Agricultural Science; Vol 16 No 1 (2018), 2018)
Culled Nubian males are important for meat production in the Sudan, but nutrition is a main constraint. Sugar beet is recently introduced for sugar production in the Gezira State and is a valuable feed. Seewa is sorghum cobs residue with low nutritive value and could be supplemented to improve the nutritive value and animals performance. There is no information on using upgraded Seewa and dried sugar beet root (DSBR) based concentrates level on Nubian kids performance and carcass characteristics. Consequently, 12 Nubian male kids at 6 month old were used to furnish this vital information. They were weighed and allocated at random to three experimental feeds and housed in individual pens with feed and water trough. They were fed upgraded Seewa (UGS) ad lib . at 8 am and 4 pm and refusals were collected, weighed and stored for laboratory analysis. The animals were fed DSBR based concentrates at 0 (control), 250g and 500g in two meals before UGS. Samples of feeds and refusals were stored for laboratory analysis. The animals were allowed a two weeks preliminary period and weighed weekly for 8 weeks. Data were statistically analyzed using ANOVA. Seewa had low CP and high CF and upgrading increased CP. Mean upgraded Seewa DMI varied among concentrates levels, but not significant (P>0.05) and were highest in animals fed 250g concentrates and least in animals fed 500g concentrates. Mean total dry matter intake (TDMI) increased significantly (P<0.05) with concentrates level. Mean water intake, body weight (BW), weekly weight gain and feed conversion ratio (FCR) increased with concentrates level, but differences were not significant (P<0.05). It was recommended to use DSBR based concentrates and upgraded Seewa in fattening Nubian male kids           ذكور الماعز النوبي المستبعدة من القطيع هامة  لإنتاج اللحوم في السودان الا أن التغذية عائق رئيسي. تم مؤخرا إدخال زراعة بنجرالسكر لإنتاج السكر في ولاية الجزيرة و هو علف  قيم. السيوة هي مخلفات قندول الذرة الرفيعة مع إنخفاض القيمة الغذائية ويمكن دعمها لتحسين القيمة الغذائية وأداء الحيوانات. لا توجد معلومات عن استخدام السيوة المحسنة وأثر مستوى عليقة مركزة ترتكز على جذر بنجر السكر المجفف علي أداء جديان ذكور الماعز النوبي وصفات الذبيحة. لذلك إستخدمت 12 ذكراً من الماعز النوبي بعمر خمسه أشهر لتوفير هذه المعلومات الضرورية. وزنت الحيوانات وتم توزيعها عشوائياً لثلاثة مجموعات وخضعت لثلاثة أعلاف بصورة عشوائية كاملة  ووضعت في حظائر مفردة بها معالف وشرابات. غذيت الحيوانات بمخلفات قناديل الذرة المحسنة حسب الرغبة عند الساعه الثامنة صباحاً والرابعة مساءاً وجمعت مخلفاتها ووزنت وحفظت لتحليلها في المعمل. كما تمت تغذية الحيوانات  بالعلف المركز عند صفر ( الشاهد) و250 جرام  و500 جرام في وجبتين قبل مخلفات قناديل الذرة المحسنة. عينات الأعلاف والمخلفات تم حفظها لتحليلها في المعمل. وزنت الحيوانات أسبوعياً لفترة ثمانية أسابيع مع أسبوعين فترة تمهيدية. تم تحليل البيانات إحصائياً بالأنوفا. تميزت السيوة بنسب بروتين منخفضة ونسب الياف خام مرتفعة وزاد التحسين نسب البروتين. إختلفت الكميات الكلية للمادة الجافة المأكولة من مخلفات قناديل الذرة المحسنة بين مستويات العليقة المركزة ولكن ليس بشكل معنوي وكان عالياً في الحيوانات التي غذيت علي 250 جرام  من العليقة المركزة وأقل في الحيوانات التي غذيت علي 500 جرام من العليقة. زاد المتوسط الكلي لكمية العلف المأكولة على أساس الوزن الجاف زاد بشكل معنوي مع مستوى العليقة المركزة. زاد متوسط استهلاك الماء ووزن الحيوانات والوزن المكتسب اسبوعيا و كفاءة استغلال العلف مع مستوى العليقة المركزة بشكل غير معنوي. يوصي بإستخدام جذور بنجر السكر المجففة مع قناديل الذرة  المحسنة لتسمين ذكور الماعز النوبي.